Wildlife Hunting and Utilization in Ulu Baleh, Sarawak, Malaysian Borneo - Cheok Ka Yi, Melynda; Mohd-Azlan, Jayasilan (Ethnobiology Letters, 2020)
Poaching is one of the greatest immediate threats and a serious conservation challenge facing wildlife in Borneo. Medium- to large-sized mammals, while charismatic, are hunted for consumption and sale. This study focuses on wildlife hunting and utilization of selected communities in a remote area in Sarawak, conducted using interview surveys within communities who hunt wildlife in Ulu Baleh. The calculated hunting pressure index in Ulu Baleh (2.24) is considered low compared to other parts of Sarawak. Local communities are dependent on wildlife protein and medicine. Even though the common hunting offtake included the bearded pig and deer species, for the hunter’s own consumption, hunters were opportunistic in taking non-target species and selling surplus meat. Lack of awareness of the implications of unsustainable hunting and difficulty in monitoring by the relevant authorities appear to be the main challenges to wildlife conservation in the area. This paper highlights the lack of research documenting wildlife utilization in the Ulu Baleh region and the implication of these results are particularly important for future adaptive wildlife management, especially for species of conservation importance in Sarawak.